IMPROVING STUDENTSâ ORGANIZING IDEAS IN WRITING ANALYTICAL EXPOSITION TEXT WITH MIND MAPPING TECHNIQUE - Anggrayani, Melawati; Sofwan, Ahmad; Saleh, Mursid (English Education Journal, 2015)
This article is a report of an action research project conducted in writing class for eleventh graders of state senior high school 2 Bae Kudus in academic year 2013/2014. The objectives of this study are to describe (1) the problems faced by the students in organizing ideas in writing analytical exposition text (2)how mind mapping technique is implemented (3) how Mind mapping technique can improve the organizing ideas in writing analytical exposition texts. The result from the observation sheet and questionnaire showed that (1) the students still used bahasa indonesia in their writing analytical exposition text (2) by using mind mapping technique studentsâ writing skill from each cycle is increased (3) studentsâ score of writing skills from precycle to cycle 1 increased 14.7 points, from cycle 1 to cycle 2 increased 12.3 points from cycle 2 to cycle 3 increased 16.6 points. So the study concluded that the implementation of mind mapping technique (1) could solve the problems faced by the students in writing analitycal exposition text (2) could improve studentsâ organizing ideas in writing analytical exposition text.